Allometric Optimization of Enrofloxacin Dosage in Growing Male Turkeys: Empirical Evidence for Improved Internal Exposure - Błażej Poźniak; Marta Tikhomirov; Karolina Motykiewicz-Pers; Kamila Bobrek; Marcin Świtała (MDPI AG, 2020)
Rapid weight gain in turkeys causes a major change in the pharmacokinetics of drugs, leading to age-dependent variability in the internal exposure and, possibly, treatment failure and/or selection for antimicrobial resistance in young individuals. The aim of the study was to investigate whether a non-linear dosing protocol that accounts for the previously established allometric relation between enrofloxacin clearance and body weight (BW) may optimize the internal exposure to enrofloxacin in growing male turkeys. Enrofloxacin was administered four times, between the age of 5 and 16.5 weeks, when the turkeys' BW increased from 1.47 to 14.92 kg. Enrofloxacin was given intravenously (i.v.) or orally at the dose calculated as follows: Dose = 30 × BW0.59. After i.v. administration, the internal exposure to the drug-quantified as the area under the concentration-time curve (AUC)-was showing little age-related variation. The coefficient of variation (CV) for AUC in all individuals (15.7%) was only slightly higher than within the age groups (5.4-13.7%). After oral drug administration, CV for AUC in all individuals (22.1%) was similar as within the age groups (8.7-32.2%). These results show that intra-species allometric scaling may be efficiently implemented in the non-linear approach to enrofloxacin dosage in turkeys in order to obtain a precise internal exposure for the optimal antimicrobial effect.